Synthesis of Three New Tricyclic Ring Systems: Pyrrolotriazepines Condensed with an Imidazole, a Triazole, or a Tetrazole Ring - Milen, Mátyás; Földesi, Tamás; Dancsó, András; Simig, Gyula; Volk, Balázs (Synlett, 2015)
In a previous paper, we have disclosed a practical synthesis of 1-aryl-3H-pyrrolo[2,1-d][1,2,5]triazepin-4(5H)-ones. Now, these compounds have been used as the starting materials for the synthesis of three new ring systems, pyrrolotriazepines condensed with an imidazole, a triazole, or a tetrazole ring. The newly synthesized compounds are structurally closely related to tricyclic derivatives known from the literature as strong anticonvulsant agents.
Keywords: nitrogen; ring closure; condensation; reduction; alkylation; sulfur